Molecular characterization of the murine Leydig cell lines TM3 and MLTC-1 - Schröder-Lange, Sarah K.; Hardt, Katharina S.; Keller, Diandra T.; Pinoé-Schmidt, Manuela; Buhl, Eva M.; Weiskirchen, Ralf (Frontiers in Endocrinology, 2025)
IntroductionLeydig cells (LCs) are located in the interstitium of the testes and are characterized as steroid hormone-producing cells that are crucial for testicular function in maintaining spermatogenesis. Disruptions in their function, for instance due to genetic defects, endocrine disruptors, or age-related changes, often lead to hypogonadism and are among the main causes of male infertility. Therefore, reliable in vitro models are crucial for understanding the underlying signaling pathways, developing new therapeutic approaches and testing toxic substances that interfere with these processes. However, as primary LCs are naturally rare, require time-consuming isolation from animals and yield only small quantities, in theory, permanent LC lines offer a more practical and reproducible alternative.MethodsWe used non-tumorigenic TM3 cells and tumorigenic MLTC-1 cells, two commercially available LCs, and subjected them to a comprehensive molecular and genetic comparative analysis.Results and discussionLight microscopy and F-actin staining by Phalloidin revealed the typical polygonal LC shape of both cell lines growing in clusters with tight cell-cell contacts. Both cell lines contain endogenous lipid droplets (LDs) and synthesis was inducible with oleic acid. Transcriptomic analysis and RT-qPCR verified the expression of different steroidogenesis-associated LD genes including members of the PLIN family and lipolysis enzymes (e.g. Pnpla2, Lipe, MgII). In addition, we identified a comprehensive panel of steroidogenesis genes via RT-PCR, RT-qPCR and Western blot analysis in MLTC-1 cells, but these were not detectable in TM3 cells. In contrast to the originally described response to gonadotropins in TM3 cells, RNA sequencing revealed no Lhcgr expression and the cells are not responsive to stimulation with human chorionic gonadotropin (hCG). MLTC-1 cells are positive for Lhcgr and respond to hCG administration with strong StAR induction on the protein and mRNA level. Short tandem repeat (STR) profiling confirmed the authenticity of both cell lines used in our study. Taken together, comprehensive molecular characterization, which includes next generation sequencing (NGS)-based transcriptome analysis and STR profiling, is essential in confirming the validity of cell models and enhancing their significance in infertility research and endocrine toxicology.